The Practise of Brand Management on Small Culinary Enterprises, An Explorative Study Using In-Dept Interview - Handari, Astrid; Iskandar, Budi Permadi (Journal of Business and Management, 2012)
Brand has been a part of almost every company, especially a big one that exists nowadays. It is a statement, an image, a message, which packed and delivered to the customer, so that they know what the company stands for. Nowadays, intense competition of a small business requires each business to be able to "fly over the crowd" that will not make them go down with the other competitors whom not able to follow the current change regarding the situation on the market.Â  As for one SME, in order to be able to fly over the crowd, the owner needs to know how to build and maintain the corporate brand. It is vital to be different in the crowded market so that the brand will not easily forgotten by the customer. However some of branding literature states that many SME pay little or no attention at all on Branding ( Frank, 2005) also most of branding literature were based on multi-national company. The objectives of this research is to find out how small-medium entrepreneur focusing in culinary business in Bandung City takes action on branding activity. Â  In order to fulfill the objectives of this research, a qualitative case study method was undertaken with 12 SME focusing in culinary industry in Bandung city. This step was taken to understand the phenomenon of small-medium-culinary entrepreneur branding activity by analyzing the clearly defined step-by-step corporate brand building activity the SME do refer to the theory of previous research about corporate brand building activity through different stages of business growth. (Mari Jununten,2010) The research approach utilized an in-dept interview with the owner or manager of the business. The findings of this study reveal new activity such as building relationship with community, managing relationships with community and customer also reputation management system using social media which never been discussed in the existing theory used in the previous research and the findings will demonstrate a condition of how far the small-medium-culinary entrepreneur takes action about branding activity. Key Words : Brand, Brand Building Activity, Brand Management, Small to Medium Enterprises, Culinary. Category: Marketing